2022
DOI: 10.6007/ijarbss/v12-i2/12152
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of the Use of Cognitive and Metacognitive Strategies in Foreign Language Learning

Abstract: Learning foreign language is challenging, especially so without a proper learning approach to the language. Therefore, one should equip oneself with suitable language learning strategies. Teachers should be perceptive of different language learning strategies in learners and which strategies they benefit the most. This quantitative research is carried out to investigate how learners use cognitive and metacognitive strategies in learning French as a foreign language. The instrument used in the study is a survey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 5 publications
1
7
0
Order By: Relevance
“…Most learners agreed that when they are confused about something they are reading for the online Mandarin class, they will figure it out after the lesson. The findings of this study were in line with a previous study (Idris et al, 2022) in which learners use both cognitive and metacognitive strategies when learning a foreign language and where there is a harmonious balance between both strategies. Another study (Isa et al, 2022) also showed that both cognitive and metacognitive strategies were used by learners in learning foreign language but female learners reported using cognitive and metacognitive strategies more often than males.…”
Section: Summary Of Findings and Discussionsupporting
confidence: 91%
“…Most learners agreed that when they are confused about something they are reading for the online Mandarin class, they will figure it out after the lesson. The findings of this study were in line with a previous study (Idris et al, 2022) in which learners use both cognitive and metacognitive strategies when learning a foreign language and where there is a harmonious balance between both strategies. Another study (Isa et al, 2022) also showed that both cognitive and metacognitive strategies were used by learners in learning foreign language but female learners reported using cognitive and metacognitive strategies more often than males.…”
Section: Summary Of Findings and Discussionsupporting
confidence: 91%
“…The instrument can be applied for the detection if the language teachers discern the role of classroom interaction in students learning. This aspect should be viewed as the positive signal for language teaching development (Idris et al, 2022). Many decades ago, literature documented the theoretical, pedagogical, and empirical evidence of the role of teacher-student interaction in facilitating second language learners learning (Long, 1996cited in Nguyen, 2020Swain, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, many researchers have revealed the role of metacognitive awareness in reading comprehension. (Barnett, 1989;Carrell & Floyd, 1987;Chamot, 2005;Gou, 2008;Idris et al, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Furthermore, the relationship between metacognition and reading comprehension seems to engage firmly, in other phrases, the reading comprehension stage may rely on the notion of character metacognition. Although a few preceding research on metacognition claimed that there's a relationship between individuals' metacognition and his/her studying comprehension performance (e.g., Ahmed, 2020;Idris et al, 2022;Maftoon & Fakhri Alamdari, 2016;Taherkhani et al, 2022). Some research revealed that there is no relationship between them, along with the research performed with the support of (Alsamadani, 2014;Mehrdad et al, 2012;Meniado, 2016;Estacio, 2013).…”
Section: Introductionmentioning
confidence: 99%